Test/Retest Variability of the eCAP Threshold in Advanced Bionics Cochlear Implant Users. Issue 6 (November 2019) - Stronks, H. Christiaan; Biesheuvel, Jan Dirk; de Vos, Johan J.; Boot, Martijn S.; Briaire, Jeroen J.; Frijns, Johan H. M.
Abstract : Objective: The reliability of the electrically evoked compound action potential (eCAP) threshold depends on its precision and accuracy. The precision of the eCAP threshold reflects its variability, while the accuracy of the threshold shows how close it is to the actual value. The objective of this study was to determine the test/retest variability of the eCAP threshold in Advanced Bionics cochlear implant users, which has never been reported before. We hypothesized that the test/retest variability is dependent on the presence of random noise in the recorded eCAP waveforms. If this holds true, the recorded error should be reduced by approximately the square-root of the number of averages. As secondary objectives, we assessed the effects of the slope of the amplitude growth function (AGF), cochlear location, and eCAP threshold on eCAP threshold precision. We hypothesized that steeper slopes should result in better precision of the linearly extrapolated eCAP threshold. As other studies have shown that apical regions have steeper slopes and larger eCAPs, we recorded eCAPs in three different cochlear locations. The difference of the precision between two commonly applied stimulus-artifact reduction paradigms on eCAP threshold precision was compared, namely averaging of alternating stimulus polarities (AP averaging) and forward masking (FM). FM requires the addition of more waveforms than AP averaging, and hence we expected FM to have lower precision than AP. Design: This was an unmasked, descriptive, and observational study with a cross-over (repeated measures) design that included 13 subjects. We recorded eCAPs on three electrode contacts: in the base, middle, and apex of the cochlea at 10 stimulus intensities. Per stimulus level, 256 eCAP waveforms were recorded. eCAP thresholds were determined by constructing AGFs and linear extrapolation to zero-amplitude. The precision of the eCAP threshold was calculated as the SD using a Monte Carlo simulation, as a function of the number of waveform averages. Results: The SD of the eCAP threshold was reduced by approximately the square root of two when the number of averages in the eCAP waveforms was doubled. The precision was significantly better when the slope of the AGF was steeper and was more favorable in the cochlear base than in the apex. Precision was better when AP averaging was used. Absolute eCAP threshold did not significantly affect precision. At the default number of 32 waveform averages in the Advanced Bionics system, we report a median SD of the eCAP threshold of 2 to 3 μA, with a range of 1 to 11 μA across the cochlea. Previous studies have shown that the total error, based on the 95% confidence bounds of the linear extrapolation, can be as high as −260 to +120 μA. Conclusions: The median variability in the eCAP threshold proved to be small compared with the total variability introduced by the linear extrapolation method. Yet there was substantial intersubject variability. Therefore, we recommend monitoring the SD during eCAP recording to facilitate informed decisions when to terminate waveform collection. From a precision perspective, AP averaging is preferable over FM as it has better precision, while fewer recordings are needed, making it the more time-efficient method of the two.